The Effect of Cross Sectional Area of Tube on Friction Factor and Heat Transfer Nanofluid Turbulent Flow - K., Kadirgama; Adnan, M. Husein; Sharma, Korada Viswanatha; R. A., Bakar (Elsevier, 2013)
The effects of the tube specifications on the heat transfer in car radiator are significant to improve cooling system performance. Friction factor and heat transfer enhancement of three types of nanofluids flow through horizontal three shapes of tubes has been evaluated numerically. CFD model by using FLUENT software depending on finite volume method was conducted. TiO2 nanoparticles with volume fractions (1%, 1.5%, 2% and 2.5%) are suspended in water as a basefluid tobenanofluids is used in this study. On the other hand, three types of tubes (circular,elliptical and flat tube) are chosen with 3 mm hydraulic diameter and 500 mm length. Numerical results show that the increase in volume fraction of nano fluid due to increase influid flow characteristics and heat trans-fer enhancement as compared with base fluid. The results of CFD model are compared with experimental data available in literature, and there is a good agreement with deviation 2%.